Pleurotus nebrodensis : a very special mushroom - Gargano, Maria Letizia; Zervakis, Georgios I.; Venturella, Giuseppe (Bentham Science Publishers, 2013)
First described by Giuseppe Inzenga in 1863 as ""the most delicious mushroom of the Sicilian mycological flora"", Pleurotus nebrodensis remains today a prized species, especially in the Mediterranean. Pleurotus nebrodensis was sought after since ancient times as a delicious mushroom in the Madonie mountains of Sicily. Tourists and local people can appreciate the organoleptic qualities of the mushrooms in restaurants where delicious cuisine are prepared with raw or cooked mushrooms. However, its appearance and numbers are declining in nature and this species has been categorized as 'CR' (Criti.